Humanism and didactic theorems from the early modern era in the knowledge society. (3rd March 2021) - Cerna, Miloslava
The paper is conceived as a debate on humanist values and educational theorems that are still favourable and topical at our era. These principles meet requirements on innovations coming from the development of technologies and economics with their consequences on society, culture and education. Blended learning is a flexible concept with the potential to reflect demands of society and market on education as well as is able to incorporate technology into the process of education. Didactic principles formulated nearly 400 years ago are permanent constituent of the design and management of teaching and learning in the virtual space as well as in in-class education. This paper shows how the didactic ideas go through the centuries, keep continuity and give a kind of order to the process of education. Examples of selected educational principles in the language e-courses are described in the practical part of the paper.